Co-Adsorption of Mixed Cationic/Non-Ionic Surfactants on a Quartz Surface - Mohsen Nikoorazm; Jayashree Nagarkar; Sharad Dixit (Adsorption Science & Technology)
The co-adsorption of binary mixtures of tetradecyltrimethylammonium bromide (TTAB) and nonyl phenyl ethoxylates (NP-n series) from their aqueous solutions on to quartz has been studied. None of the ethoxylates adsorbed on to the quartz when alone, but considerable adsorption took place from the mixture with cationic TTAB. The adsorption of TTAB was increased in the presence of ethoxylates below its CMC due to chain–chain interaction between the cationic/non-ionic surfactants. FT-IR spectroscopic studies indicated that micelle-like aggregate structures formed on the quartz surface even below the CMC. Zeta potential measurements were carried out in order to understand the adsorption behaviour.